Interview of Enid Turyahikayo, Assistant Audit and Compliance Officer, NEMA, Uganda - Turyahikayo, E. (International Livestock Research Institute, 2014)
Interviews of selected participants; views from the Regional Experts Workshop on Industrial Effluents Management in East Africa held on 19-20 May 2014, Ethiopia